Developing rural Chinese children's computational thinking through game-based learning and parental involvement. Issue 1 (2nd January 2023) - Zhang, Xiangling; Tlili, Ahmed; Guo, Junhong; Griffiths, David; Huang, Ronghuai; Looi, Chee-Kit; Burgos, Daniel
Abstract: The lack of teachers and equipment is a major obstacle to the implementation of Computational Thinking (CT) in education, particularly for rural schools. Although CT education has been investigated for many years, less attention has been paid to lower primary schools in rural areas. This study contributes to filling this gap by investigating the impact of three different learning approaches on the CT of grade-two primary school students in a rural area in China. Seventy-seven students were randomly assigned to three learning approaches, namely traditional lectures, Game-Based Learning (GBL) using a newly designed board game in classrooms, and GBL with parental involvement. The findings showed that both GBL approaches (i.e., with and without parents) significantly enhanced the students' CT skills compared to the traditional approach. The findings also showed that the GBL approach with parental involvement significantly enhanced students' attitudes toward learning CT compared with the other two approaches.